Emerging threat of ranavirus: prevalence, genetic diversity, and climatic drivers of Ranavirus (Iridoviridae) in ectothermic vertebrates of Asia - Herath, Jayampathi; Sun, Dan; Ellepola, Gajaba; Subramaniam, Kuttichantran; Meegaskumbura, Madhava (Frontiers in Veterinary Science, 2023)
Ranavirus disease, caused by viruses within the genus Ranavirus (Iridoviridae), is considered a globally emerging infectious disease linked to mass mortality events in both wild and cultured ectothermic vertebrates. Surveillance work is, however, limited in Asia hence prevalence and the dynamics of the disease remain poorly understood. To understand disease burden and the potential biotic and abiotic drivers in southern China region, we conducted a systematic surveillance of the ranavirus across Guangxi Zhuang Autonomous region (GAR). For this, we used a multifaceted approach involving screening of amphibians and other potential hosts, diagnostic tests, phylogenetic analyses, prevalence estimation, co-infection assessments, and climatic niche analyses. Over one thousand individuals were sampled across 25 sampling sites. We found ninety-two individuals from 18 species of ectothermic vertebrates to be infected with ranavirus. Two lineages were responsible -Rana nigromaculata ranavirus and tiger frog virus were identified using phylogenetic analysis based on the major capsid protein (MCP) gene fragment. Out of these two lineages, the presence of tiger frog virus is rare as we came across only one case. We also found evidence of a co-infection with ranavirus and Batrachochytrium dendrobatidis that can be highly detrimental to host populations; This is a provisional file, not the final typeset article possibly the first such documentation in Asia. Our niche modelling analysis suggests that precipitation seasonality plays an important role in ranavirus prevalence in GAR -southwestern, southeastern, central and northeastern regions of GAR can be considered to be optimum habitats for ranaviruses. Infection rates in wild frog species have reached 100% in some areas, even in nature reserves. Our research also indicates that culture facilities and pet farms are frequently infected, serving as likely vectors for the regional and global spread of ranaviruses. The knowledge generated suggests the need for systematic surveillance, stringent biosecurity measures, and control of international animal trade to prevent further transmission and protection of biodiversity and aquaculture industries across Asia.